2019
DOI: 10.3390/brainsci9070171
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin Releasing Factor Type 1 and 2 Receptor Signaling in the Medial Prefrontal Cortex Modulates Binge-Like Ethanol Consumption in C57BL/6J Mice

Abstract: Corticotropin releasing factor (CRF) signaling via limbic CRF1 and 2 receptors (CRF1R and CRF2R, respectively) is known to modulate binge-like ethanol consumption in rodents. Though CRF signaling in the medial prefrontal cortex (mPFC) has been shown to modulate anxiety-like behavior and ethanol seeking, its role in binge ethanol intake is unknown. Here, we used “drinking-in-the-dark” (DID) procedures in male and female C57BL/6J mice to address this gap in the literature. First, the role of CRF1R and CRF2R sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the current study have yet to address the involvement of neuropeptide signaling, especially that of somatostatin, in modulating alcohol consumption. Previous reports have demonstrated that DID reduces NPY expression in the PL, and conversely intra-PL administration of NPY1 agonist and CRF1 antagonist could reduce alcohol binge drinking (17,16). Here we did not assess whether the effects of hM3Dq-induced excitation of PL SST neurons on alcohol binge drinking could be partially attributed to SST peptide release and SST signaling in the PL.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, the current study have yet to address the involvement of neuropeptide signaling, especially that of somatostatin, in modulating alcohol consumption. Previous reports have demonstrated that DID reduces NPY expression in the PL, and conversely intra-PL administration of NPY1 agonist and CRF1 antagonist could reduce alcohol binge drinking (17,16). Here we did not assess whether the effects of hM3Dq-induced excitation of PL SST neurons on alcohol binge drinking could be partially attributed to SST peptide release and SST signaling in the PL.…”
Section: Discussionmentioning
confidence: 91%
“…Intragastric administration of high ethanol doses in rats (5 g/kg) diminished GABAA receptor-mediated inhibitory currents in PFC layer 5/6 pyramidal neurons accompanied by a reduction in expression of the α1 GABAA receptor subunit (50). As pyramidal neurons are the main group of projection neurons from the PL, providing strong glutamatergic input to associated cortical regions (6,7), nucleus accumbens (10), ventral tegmental area (51) and amygdala (52), which are critically involved in emotional and intra-PL administration of NPY1 agonist and CRF1 antagonist could reduce alcohol binge drinking (17,16). Here we did not assess whether the effects of hM3Dq-induced excitation of PL SST neurons on alcohol binge drinking could be partially attributed to SST peptide release and SST signaling in the PL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orozco-Cabal and colleagues demonstrated that chronic cocaine results in increased functionality of presynaptic CRF-R2 and loss of postsynaptic function of CRF-R1 in the PFC of male rats. Moreover, an interesting, recent study found that inhibition of CRF-R2 and separate activation of CRF-R1 in the PFC both resulted in decreased binge-like ethanol consumption in male and female C57BL/6J mice, confirming that much like in the CEA, these two receptors may play opposite roles in substance use (Robinson et al, 2019b). In this work, Robinson et al (2019b) demonstrated that co-administration of CRF-R1 and CRF-R2 antagonists attenuated the behavioral effect of CRF-R1 antagonist.…”
Section: Substance Use Disorders (Pre-clinical and Clinical Evidence)mentioning
confidence: 89%
“…Moreover, an interesting, recent study found that inhibition of CRF-R2 and separate activation of CRF-R1 in the PFC both resulted in decreased binge-like ethanol consumption in male and female C57BL/6J mice, confirming that much like in the CEA, these two receptors may play opposite roles in substance use (Robinson et al, 2019b). In this work, Robinson et al (2019b) demonstrated that co-administration of CRF-R1 and CRF-R2 antagonists attenuated the behavioral effect of CRF-R1 antagonist. This suggests that decreased binge-like ethanol drinking resulting from inhibition of CRF-R1 may result from increased activation of the CRF-R2, providing strong evidence in support of an important role of both CRF-R1 and CRF-R2 in the PFC in regulating substance abuse.…”
Section: Substance Use Disorders (Pre-clinical and Clinical Evidence)mentioning
confidence: 89%